Foreign Direct Investment and Economic Growth in Indonesia: Role of Human Capital and Trade Openness - Setiyanto, Aris; Fitrady, Ardyanto (JEJAK, 2024)
This study examines FDI – economic growth nexus in Indonesia throughout 1970 to 2019. It also focuses on analyzing whether FDI-human capital and FDI-trade openness complement each other to enhance economic growth. Employing the autoregressive distributed lag (ARDL) bound test and fully modified ordinary least square (FMOLS), the study find cointegrated relationship between FDI and economic growth. Specifically, the interaction between FDI and human capital is statistically non-significant to long-term growth. However, interestingly FDI and trade openness complement each other to encourage long-term growth. From the policy perspective, this study supports the improvement of the quality of human capital to enhance the benefits of a foreign presence in the economy and further reforms in the trade sector to enhance long-term growth in Indonesia.